(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
The global expansion of English has led to its widespread use as a lingua franca among speakers from diverse linguistic and cultural backgrounds. This development has profound implications for English language teaching, particularly in relation to classroom norms, pedagogical practices, teacher beliefs, and assessment standards. This article examines the concept of English as a Lingua Franca (ELF) and analyzes how it challenges traditional native-speaker-oriented norms in English language classrooms. Drawing on theoretical perspectives and empirical research, the paper discusses linguistic variation, communicative effectiveness, learner identity, and intercultural competence. It further explores the pedagogical and institutional challenges of implementing ELF-informed classroom norms and considers future directions for English language education. The article argues that recognizing English as a Lingua Franca requires a fundamental re-evaluation of established classroom norms in order to better reflect the realities of global English use.